Clinical characteristics of hereditary spherocytosis with red blood cell membrane protein gene variants - Jingying Cheng; Liqiang Zhang; Jiafeng Yao; Shasha Zhao; Jin Jiang (Frontiers in Pediatrics)
The clinical manifestations of hereditary spherocytosis (HS) are often heterogeneous, spanning from asymptomatic to severe symptoms that may pose life-threatening risks. Genotype-phenotype correlations remain controversial in clinical research. This retrospective study evaluated the correlation between genetic variants and clinical characteristics in a cohort of 64 Chinese pediatric patients with HS. The predominant variants were found in the ANK1 (27 cases, 42%) and SPTB (26 cases, 41%) genes, while variants in the SPTA1 (6 cases, 9%) and SLAC4A1 genes (5 cases, 8%) were less common. No EPB42 variants were detected. A total of 71 variants were identified. Variation types included nonsense (21%), missense (27%), frameshift mutations (39%), splicing (8%), and large fragment deletions (4%). No statistical differences in hemoglobin levels, MCV, MCH, MCHC, or reticulocytes were observed across the various genetic variant groups. Bilirubin levels were remarkably elevated in patients with HS variants, and those with SPTB-HS had significantly higher bilirubin levels, including total bilirubin (p = 0.033) and indirect bilirubin (p = 0.018) compared to those with SPTA1-HS. Moreover, those with the ANK1 variants displayed reduced resistance to lysis at varying NaCl concentrations in comparison to those with the SPTA1 variants (p = 0.047). In short, patients with the ANK1 and SPTB variants had the most severe disease, while those with the SPTA1 variants had the mildest. Genetic testing is advised in patients without a family history or who are difficult to diagnose with routine laboratory tests, as this may also provide references for clinical treatment and genetic counseling.